Mapping evidence on predictors of adverse sexual and reproductive health outcomes among young women in South Africa: A scoping review - Obasanjo A. Bolarinwa; Tlou Boikhutso (AOSIS, 2021)
Background: Globally, most young women have an unmet need for sexual and reproductive health (SRH), which remains a public health concern. Identifying the predictors can help reduce this challenge. Aim: This scoping review maps evidence on predictors of adverse sexual and reproductive health outcomes among young women in South Africa. Method: Askey and O'Malley's framework guided this review. We searched five databases from January 2000 to December 2020 using relevant keywords, Boolean terms and medical subject heading terms. All relevant extracted data were organised into the study themes, and summary of all the findings were reported in a narrative format. Results: Nine studies met the inclusion criteria out of 1219 studies identified. Four out of the nine studies were national-based studies, while the remaining five studies were conducted in Western Cape (two), Eastern Cape (two) and KwaZulu-Natal (one). Out of the nine studies included, three reported predictors of unintended pregnancy, while six reported predictors of sexually transmitted infections and HIV among young women in South Africa. The most prevailing predictors of adverse sexual and reproductive health outcomes were gender-based violence and alcohol use, while other predictors were lower socio-economic status, place of residence, multiple sexual partnerships, low education and being between the ages of 20-24 years. Conclusion: We conclude that gender-based violence and alcohol abuse are the most prevailing predictors of adverse sexual and reproductive health outcomes among young women in South Africa.